Topical Nifedipine Administration for Secondary Prevention in Frostbitten Patients - Carceller, Anna; González Torcal, Juan Pedro; Viscor, Ginés (Frontiers in Physiology, 2020)
Frostbite is a cold related injury with growing incidence among healthy subjects. Sequelae after frostbite are frequent and variable among individuals. We studied the thermal response in the digits of hands and feet considering three different conditions: healthy, frostbite without amputation and frostbite with amputation of five subjects who had suffered frostbite in the past but were fully recovered from their injuries. Three immersions in cold water were performed, followed by a 30 minutes of limb temperature recovery. Then the effect of a topical 10% nifedipine preparation was evaluated. After applying the preparation, three new consecutive immersions in cold water were performed. Immediately after each immersion, the individual digits temperature from hands and feet was assessed using thermography. We found different thermal responses among the different digits of hands and feet even without nifedipine treatment. Nifedipine showed a cooling effect when applied in healthy and amputated tissues without thermal stress. In cold conditions, it ameliorated the cold response in healthy digits but caused a negative effect on amputated ones. Regarding toes, topical nifedipine at this concentration showed detrimental effects in all conditions. Topical nifedipine application can be considered as a good tool for preservation of healthy digits exposed to cold with the adequate thermal insulation, but the potentially harmful effects of this treatment on previously frostbitten tissues has to be taken into account. More research is required to elucidate the impact of a topical preparation of nifedipine on the secondary prevention at mild temperatures in distal tissues previously frostbitten without amputation.